IDENTIFIKASI JENIS BAKTERI PADA UTERUS SAPI PERAH NORMAL - , NILAM KUSUMASTUTI; , Dr. drh. Surya Agus Prihatno, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Productivity of dairy cows in Indonesia are still low due to various factors mainly related to reproductive management. One reason for the low reproductive efficiency in cattle is the existence of reproductive disorders caused by bacterial infections. The presentresearch was conducted to determine bacterial content of dairy cow's uterine with a normal marital history. Bacterial isolation and identifications were applied on seven uterine fluid samples taken from Friesian Holstein dairy cows that have normal marital history in Sleman. Sampling was done by flushing method using sterile distilled water. Samples were analysed in the Laboratory of Microbiology, âBalai Besar Veteriner (BBVET)â Wates. Data resulting from the isolation and identification of bacteria from normal uterine dairy cows were analyzed with descriptive methods. The results show that bacterial species found in the normal uterine dairy cowswere Bacillus sp., Staphylococcus sp., Eserichia coli, and Streptococcus sp.